The Healing Hands - Jasmine Riddle (Stimulus: A Medical Humanities Journal, 2023)
It is well known that we use our hands for the majority of tasks we complete on a daily basis. In fact, there are not many tasks that we can complete without the use of our hands. Some of the ways doctors and health professionals use their hands in the medical field include surgeries, palpating a patient, and to document any information gathered about the patient. What if there was a way to heal someone just by using their hands? It turns out this is possible due to a naturopathic treatment called Reiki. Reiki is an ancient Japanese technique in which the healer will either hover their hands or lightly place their hands on the patient and transfer healing energy to the person receiving the treatment. In my illustration, the colors of the background resemble the seven chakras in the body and the hands are hovering around the center as if they are receiving healing energy.